Experimental studies on segmental cortical bone xenografts in dogs - Mohamed Said Mostafa Amer; Mohamed Taha Ibrahim Elkeiey; Shaaban Mohamed Gad Allah; Sherein Saied Abdelgayed (Cairo : Mohamed Said Mostafa Amer, 2009)
The present study was designed into two main stages stage 1, 50 native breed adult goats were used as donors for done grafts clean harvesting method was used for collection of bone grafts followed by autoclave sterilization ( 121(NO(BC / 30 minutes )s
Thesis (M.Sc.) - Cairo University - Faculty of Veterinary Medicine - Department of Surgery-Anesthesiology-Radiology
Issued also as CD
Keywords: Cortical; Segmental; Xenograft dog